MANFAAT KEGIATAN DOA ROSARIO BAGI PERKEMBANGAN IMAN ANGGOTA KOMUNITAS DOA ROSARIO SUCI PAROKI ST.WILLIBRORDUS CEPU - Tasyiana, Tasyiana; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
From the early Church to the present day, the Rosary continues to be popular among Christians. In the Middle Ages there was even an association of the Holy Rosary Society, and today one of these associations is in St.Willibrordus Cepu Parish with the name Holy Rosary Prayer Community. This community is run by an elderly group, and has been around for 17 years. The problem: is the Rosary prayer activity that has been carried out for dozens of years really providing benefits for the development of the members' faith? This study aims to answer these problems. The research method uses qualitative research methods with interview techniques. The results showed that out of 100% of the members there were 20% who did not understand the basic concept of praying the Rosary. However, 100% of members understand the development of faith, and acknowledge that praying the Rosary is beneficial for the development of member faith. This benefit is manifested in attitudes and actions as a real reflection of the example of Our Lady and Jesus in the Rosary prayer activities.